Duplex-hairpin transitions in DNA: NMR studies on CGCGTATACGCG. - Wemmer, D E (1985)
Two dimensional NMR methods have been used to assign proton resonances in the high salt (greater than or equal to 100mM Na+), low temperature duplex form of the self-complementary DNA dodecamer d(CGCGTATACGCG). At low salt (less than or equal to 10mM Na+) and higher temperature marked changes in the two-dimensional spectrum, and in the one-dimensional spectrum reported by others, indicate that the molecule converts to an alternate conformation. Using saturation transfer methods, many of the resonances of this new conformation have been assigned, and the kinetics of the interconversion of the two forms has been studied. The linewidth, correlation time, and concentration dependence of the formation of this alternate conformation support the idea that it is a unimolecular hairpin. Observation of chemical shifts and NOEs in the hairpin conformation allow some preliminary structural characterization. Examination of the energetics of the interconversion suggests that the exchange between forms does not proceed through a single stranded intermediate, but rather through another pathway, probably involving a cruciform structure.